Structural changes in elastically stressed crystallites under irradiation; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 352 : Computer Simulation of Radiation Effects in Solids - Zolnikov K. P. Konstantin Petrovich; Korchuganov A. V. Aleksandr Vyacheslavovich; Kryzhevich D. S. Dmitry Sergeevich; Chernov V. M. Vladimir Mikhaylovich; Psakhie S. G. Sergey Grigorievich (2015, 2015)
Title screen